An improved automatic trap for capturing birds in nest boxes. Issue 3 (4th May 2019) - Zhang, Lei; Wang, Juan; Zhang, Congying; Shu, Xuetong; Yin, Jiangxia; Wan, Dongmei
Abstract : Several traps have been designed for capturing birds in their nest boxes, and questions remain concerning the effectiveness, reliability and automatism of the traps. Here we developed an automatic trap, designed to capture parent birds in artificial nest boxes. When a bird enters the nest box, the trap will be triggered by pulling on a twig treadle and the door will shut securely with a magnet. During 2014–2016, the trap was used to capture Varied tits ( Parus varius ), Marsh tits ( Parus palustris ) and Great tits ( Parus major ) during the breeding seasons. We captured 177 birds, with a trigger rate of 92.2%, a capture rate of 100% and an average capture time of 22.5 ± 19.6 min. No known trap-related injuries or desertions occurred. This light weight, easily operated, and highly efficient trap improves the data collection and results during field work. This trap can be used in a wide variety of nest boxes to capture songbirds.